2022
DOI: 10.1007/s00268-022-06575-0
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Anxiety is Associated With Postoperative Complications in Vascular Surgery: A Cross‐Sectional Study

Abstract: Background Preoperative anxiety is associated with increased morbidity and/or mortality in surgical patients. This study investigated the incidence, predictors, and association of preoperative anxiety with postoperative complications in vascular surgery. Methods Consecutive patients undergoing aortic, carotid, and peripheral artery surgery, under general and regional anesthesia, from February until October 2019 were included in a cross‐sectional study. Anesthesiologists assessed preoperative anxiety using a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…(44) Also, a strong correlation was found between preoperative anxiety and subsequent dissatisfaction with surgical treatment. (47) Finally, our previous study (6) demonstrated that high-level preoperative anxiety is associated with severe postoperative complications (postoperative mental disorders, pulmonary complications, and postoperative nausea).…”
Section: The Concequences and Significance Of Preoperative Anxietymentioning
confidence: 96%
“…(44) Also, a strong correlation was found between preoperative anxiety and subsequent dissatisfaction with surgical treatment. (47) Finally, our previous study (6) demonstrated that high-level preoperative anxiety is associated with severe postoperative complications (postoperative mental disorders, pulmonary complications, and postoperative nausea).…”
Section: The Concequences and Significance Of Preoperative Anxietymentioning
confidence: 96%
“…1,2 This anxiety is extremely common, even in individuals without any prior diagnosis of anxiety disorder, and has been associated with perioperative hemodynamic instability and, correspondingly, worse procedural outcomes. 1,3 Perioperative anxiety can be further compounded for patients with an anesthetic plan of procedural sedation and analgesia (PSA, also known as conscious sedation) as opposed to general anesthesia because they remain continuously aware of perioperative activity. 4,5 For patients undergoing peripheral vascular interventions (PVIs), PSA is often the preferred standard-of-care, because it avoids the cardiopulmonary stress of intubation, though patients need to be awake enough to comply with essential perioperative instructions from proceduralists such as holding the ipsilateral leg still and breath holds at certain intervals.…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative anxiety is associated with issues such as the need for higher doses of medication to induce anesthesia and postoperative analgesia, challenging intravenous access, and autonomic fluctuations. Furthermore, increased post-operative pain, nausea and vomiting, prolonged recovery, and increased risk of infection are associated with anxiety [ 6 ]. Various methods are used in different countries to reduce preoperative anxiety in patients.…”
Section: Introductionmentioning
confidence: 99%